2018
DOI: 10.1002/jez.2179
|View full text |Cite
|
Sign up to set email alerts
|

The vulnerability of developing embryos to simulated climate warming differs between sympatric desert lizards

Abstract: The vulnerability of species to climate warming varies along latitudinal and elevational clines, but how sympatric species vary in vulnerability to climate warming remains largely unknown. We experimentally simulated nest temperatures of two sympatric lizards with divergent microhabitat preferences (Phrynocephalus przewalskii and Eremias argus), under climate warming senarios, to determine the response of embryos to increased mean temperatures and heat waves. Our study demonstrated that simulated climate warmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 69 publications
0
19
0
Order By: Relevance
“…In addition to range contraction and a northward shift, another response pattern—range expansion—was documented in the present study. Different responses of sympatric species to climate change have been previously demonstrated, both by laboratory experiments (Logan, Huynh, Precious, & Calsbeek, ; Ma et al, ) and by SDM projections (Van Zuiden, Chen, Stefanoff, Lopez, & Sharma, ) and primarily attributed to differences in thermal sensitivity. For instance, Ma et al () experimentally tested the responses of embryos of two sympatric desert lizards to simulated climate warming and found that climate warming had different impacts on the two species studied.…”
Section: Discussionmentioning
confidence: 95%
“…In addition to range contraction and a northward shift, another response pattern—range expansion—was documented in the present study. Different responses of sympatric species to climate change have been previously demonstrated, both by laboratory experiments (Logan, Huynh, Precious, & Calsbeek, ; Ma et al, ) and by SDM projections (Van Zuiden, Chen, Stefanoff, Lopez, & Sharma, ) and primarily attributed to differences in thermal sensitivity. For instance, Ma et al () experimentally tested the responses of embryos of two sympatric desert lizards to simulated climate warming and found that climate warming had different impacts on the two species studied.…”
Section: Discussionmentioning
confidence: 95%
“…However, it is well known that nest (incubation) temperature varies considerably during embryogenesis in nature (Simoncini et al, ; Valenzuela, ). For this reason, several studies have focused on temperature fluctuations and their influence on embryonic development in turtles and lizards (Ashmore & Janzen, ; Du & Ji, ; Fuentes, Limpus, & Hamann, ; Georges, Beggs, Young, & Doody, ; Hawkes, Broderick, Godfrey, & Godley, ; Hays, Broderick, Glen, & Godley, ; Les, Paitz, & Bowden, ; Ma et al, ; Mitchell, Kearney, Nelson, & Porter, ; Patiño‐Martinez, Marco, Quiñones, & Hawkes, ; Wapstra et al, ; Witt, Hawkes, Godfrey, Godley, & Broderick, ), although this aspect has not been widely studied in crocodilians. It was also mentioned that incubation temperature influences hatchling phenotypes and quality in reptiles (Booth, , ; Noble, Stenhouse, & Schwanz, ).…”
Section: Discussionmentioning
confidence: 99%
“…Ma et al. () exposed embryos of two sympatric lizard species (that occupy different microhabitats) to climate warming scenarios and show that the impact of climate warming on these species is dependent upon preferred microhabitats. Lastly, Cunningham, Fitzpatrick, While, and Wapstra () examined the consequences of thermal conditions at the margins of the population's temperature range in a viviparous skink, and suggest that advancing birth dates due to warming climates could have positive effects for their montane population.…”
Section: Goals and Overview Of This Special Issuementioning
confidence: 99%
“…Sanger, Kyrkos, Lachance, Czesney, and Stroud (2018) demonstrated that increasing temperatures negatively affect embryo survival during the stages of morphogenesis in brown anoles, and suggest that climate change will likely negatively affect egg survival given that nests in the field are currently at the thermal limits. Ma et al (2018) exposed embryos of two sympatric lizard species (that occupy different microhabitats) to climate warming scenarios and show that the impact of climate warming on these species is dependent upon preferred microhabitats. Lastly, Cunningham, Fitzpatrick, While, and Wapstra (2018) examined the consequences of thermal conditions at the margins of the population's temperature range in a viviparous skink, and suggest that advancing birth dates due to warming climates could have positive effects for their montane population.…”
Section: Global Change Biology and Conservationmentioning
confidence: 99%